Pengaruh Corporate Social Responsibility Terhadap Tax Avoidance pada Perusahaan Manfaktur yang Terdaftar pada Bursa Efek Indonesia Tahun 2014-2017 - Farida Setiawati; Priyo Hari Adi (JIAK : Jurnal Ilmiah Akuntansi dan Keuangan, 2020)
This study aims to examine and provide empirical evidence of the influence of corporate social responsibility (CSR) against tax avoidance. The independent variables of this study are CSR, size control variables and financial performance which are proxy through leverage, the dependent variable is tax avoidance. The independent variable is measured using a corporate social responsibility index (CSRI), the size control variable is measured by total company assets, the financial performance control variable is measured by a debt to equity ratio (DER), the dependent variable tax avoidance is measured using the effective tax rate. The population used is manufacturing companies that have been listed on Bursa Efek Indonesia in 2014-2017 . The research sample was determined using 89 random sampling techniques with company data. Data processing in this study uses multiple regression analysis models (MRA). Regression analysis results show that the varibales corporate social responsibility has a positive impact on tax avoidance.